Career Path Management as a Motivational tool for Employees - Hilda , Hilda; RIZK - SORBO, Camilla (Proche-Orient Études en management, 2020)
The article tackles the concept of Career path management in Lebanese companies. As the rapidly changing environment is causing velocity, difficult for individuals to cope with in their professional lives, the literature review shows the importance of career path management as a motivational tool and as a factor influencing positively the productivity and the impact of reducing high turnover rate in companies. The contribution of the empirical part lays in the necessity of a strong focus on career path management as a process in the Human Resources department. It also reveals the concerns and the difficulties decision makers face in the proper implementation of the concept.